Structure of the mantle beneath the Alboran Basin from magnetotelluric soundings. (19th December 2015) - Garcia, X.; Seillé, H.; Elsenbeck, J.; Evans, R. L.; Jegen, M.; Hölz, Sebastian; Ledo, J.; Lovatini, A.; Marti, A.; Marcuello, A.; Queralt, P.; Ungarelli, C.; et al.
Abstract: We present results of marine MT acquisition in the Alboran sea that also incorporates previously acquired land MT from southern Spain into our analysis. The marine data show complex MT response functions with strong distortion due to seafloor topography and the coastline, but inclusion of high resolution topography and bathymetry and a seismically defined sediment unit into a 3‐D inversion model has allowed us to image the structure in the underlying mantle. The resulting resistivity model is broadly consistent with a geodynamic scenario that includes subduction of an eastward trending plate beneath Gibraltar, which plunges nearly vertically beneath the Alboran. Our model contains three primary features of interest: a resistive body beneath the central Alboran, which extends to a depth of ∼150 km. At this depth, the mantle resistivity decreases to values of ∼100 Ohm‐m, slightly higher than those seen in typical asthenosphere at the same depth. This transition suggests a change in slab properties with depth, perhaps reflecting a change in the nature of the seafloor subducted in the past. Two conductive features in our model suggest the presence of fluids released by the subducting slab or a small amount of partial melt in the upper mantle (or both). Of these, the one in the center of the Alboran basin, in the uppermost‐mantle (20–30 km depth) beneath Neogene volcanics and west of the termination of the Nekkor Fault, is consistent with geochemical models, which infer highly thinned lithosphere and shallow melting in order to explain the petrology of seafloor volcanics. Key Points: First marine MT survey in Alboran, an area of very complex topography and tectonic history Two conductive anomalies are interpreted as fluids released from the Alboran subducting plate We imaged the subducting slab as a resistor that changes its electrical properties at 200 km depth